2000
DOI: 10.1143/ptp.103.425
|View full text |Cite
|
Sign up to set email alerts
|

Comments on T-Dualities of Ramond-Ramond Potentials

Abstract: The type IIA/IIB effective actions compactified on T d are known to be invariant under the T -duality group SO(d, d; Z), although the invariance of the R-R sector cannot be seen so directly. Inspired by a work of Brace, Morariu and Zumino, we introduce new potentials, which are mixtures of R-R potentials and the NS-NS 2-form, in order to make the invariant structure of R-R sector more transparent. We give a simple proof that if these new potentials transform as a Majorana-Weyl spinor of SO (d, d; Z), the effec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
194
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(198 citation statements)
references
References 17 publications
2
194
0
Order By: Relevance
“…The aim of this subsection is to give a brief review of the democratic formulation of the bosonic sector of (massless) Type IIA and Type IIB supergravity theories [48,49] (also see [50,51]). The (bosonic) matter content of these two theories are as follows:…”
Section: Democratic Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of this subsection is to give a brief review of the democratic formulation of the bosonic sector of (massless) Type IIA and Type IIB supergravity theories [48,49] (also see [50,51]). The (bosonic) matter content of these two theories are as follows:…”
Section: Democratic Formulationmentioning
confidence: 99%
“…It can be shown that the actions given above are equivalent to the standard action of Type IIA and Type IIB supergravity theories, which also involve some complicated Chern-Simons type terms, in the following sense [37,48,49]: if one applies the duality relations (3.6) to the field equations derived from the actions (3.8), (3.9), then one obtains exactly the same field equations that one would have derived from the standard actions. The field equations for lower degree form fields match directly in the two formulations.…”
Section: Jhep09(2017)044mentioning
confidence: 99%
See 1 more Smart Citation
“…The R-R potentials are implicitly defined by (B.3). T-duality acts on these field strengths as follows [61][62][63][64]51], The virtue of using this definition is the ability to dualize backgrounds for which the R-R field strengths respect the chosen isometries, while the associated R-R potentials need not. …”
Section: B T-duality Rulesmentioning
confidence: 99%
“…More recently, the case of single T-duality in the presence of supersymmetry has also been considered in [5][6][7]. In [8,9] it was observed that the potentials C ′(n) transform in the spinor representations of the Tduality group, verified directly in [10]. Also, see [11].…”
Section: Introductionmentioning
confidence: 99%